Insights From Y-STRs: Forensic Characteristics, Genetic Affinities, and Linguistic Classifications of Guangdong Hakka and She Groups - Luo, Chunfang; Duan, Lizhong; Li, Yanning; Xie, Qiqian; Wang, Lingxiang; Ru, Kai; Nazir, Shahid; Jawad, Muhammad; Zhao, Yifeng; Wang, Fenfen; Du, Zhengming; Peng, Dehua; et al. (Frontiers in Genetics, 2021)
Guangdong province is situated in the south of China with a population size of 113.46 million. Hakka is officially recognized as a branch of Han Chinese and She is the official minority group in mainland China. There are approximately 25 million Hakka people who mainly live in the East and North regions of China while there are only 0.7 million She people. Genetic characterization and forensic parameters of these two groups are poorly defined (She) or still need to explore (Hakka). In this study, we have genotyped 475 unrelated Guangdong males (260 Hakka and 215 She) with Promega PowerPlex® Y23 System. A total of 176 and 155 different alleles were observed across all 23 Y-STRs for Guangdong Hakka (with a range of allele frequencies from 0.0038 to 0.7423) and Guangdong She (0.0047 ~ 0.8605), respectively. The gene diversity (GD) ranged from 0.4877 ~ 0.9671 (Guangdong Hakka) and 0.3277 ~ 0.9526 (Guangdong She) while the haplotype diversities (HD) were 0.9994 and 0.9939 for Guangdong Hakka and Guangdong She with discrimination capacity (DC) values of 0.8885 and 0.5674, respectively. With reference to geographical and linguistic scales, the phylogenetic analyses showed us that Guangdong Hakka has a close relationship with Southern Han, and there is an extensive gene flow between Guangdong Hakka and surrounding Han populations. Also, the predominant haplogroups of Guangdong She group were O2-M122 and O2a2a1a2-M7 while Guangdong She clustered with other Tibeto-Burman language-speaking populations (Guizhou Tujia and Hunan Tujia), which shows us that the Guangdong She group is one of the branches of Tibeto-Burman populations and the Huonie dialect of She languages may be a branch of Tibeto-Burman language families.